2022
DOI: 10.1158/0008-5472.can-21-2794
|View full text |Cite
|
Sign up to set email alerts
|

Tipping Cancer Cells Over the Edge: The Context-Dependent Cost of High Ploidy

Abstract: Tetraploidy is an aneuploidy-permissive condition that can fuel tumorgenesis. The tip-over hypothesis of cytotoxic therapy sensitivity proposes that therapy is effective if it pushes a cell's aneuploidy above a viable tipping point. But elevated aneuploidy alone may not account for this tipping point. Tissue microenvironments that lack sufficient resources to support tetraploid cells can explain the fitness cost of aneuploidy. Raw materials needed to generate deoxynucleotides, the building blocks of DNA, are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…These observations suggest that cell type- and/or tissue-specific factors other than the physiological levels of tetraploidy may determine whether WGD prevents or promotes cancer. For instance, nutrient availability may be an important factor for the expansion of tetraploid cell populations in different tissues ( Kimmel et al, 2020 ; Andor et al, 2022 ). Experimental findings have demonstrated that WGD often triggers a p53-mediated cell cycle arrest in non-transformed cells ( Andreassen et al, 2001 ; Kuffer et al, 2013 ), which can be overcome by some tetraploid cells if the p53, Rb, and/or Hippo pathways are disrupted or if cyclin D and/or E are over-expressed ( Andreassen et al, 2001 ; Fujiwara et al, 2005 ; Castedo et al, 2006 ; Ganem et al, 2014 ; Crockford et al, 2017 ; Zeng et al, 2023 ).…”
Section: Is There a Link Between Whole Genome Doubling And Centrosome...mentioning
confidence: 99%
“…These observations suggest that cell type- and/or tissue-specific factors other than the physiological levels of tetraploidy may determine whether WGD prevents or promotes cancer. For instance, nutrient availability may be an important factor for the expansion of tetraploid cell populations in different tissues ( Kimmel et al, 2020 ; Andor et al, 2022 ). Experimental findings have demonstrated that WGD often triggers a p53-mediated cell cycle arrest in non-transformed cells ( Andreassen et al, 2001 ; Kuffer et al, 2013 ), which can be overcome by some tetraploid cells if the p53, Rb, and/or Hippo pathways are disrupted or if cyclin D and/or E are over-expressed ( Andreassen et al, 2001 ; Fujiwara et al, 2005 ; Castedo et al, 2006 ; Ganem et al, 2014 ; Crockford et al, 2017 ; Zeng et al, 2023 ).…”
Section: Is There a Link Between Whole Genome Doubling And Centrosome...mentioning
confidence: 99%
“…That ploidy and cancer type are confounded prevents any causal conclusions to be drawn from this analysis. This correlation is however to be expected, because ploidy is highly cancer types specific [7274].…”
Section: Methodsmentioning
confidence: 99%
“…267,[427][428][429][430][431][432][433][434][435][436][437] Despite these challenges, recent advances suggest promising possibilities for a new, personalized, CIN-specific approach to anti-tumor therapy. 358,406,410,411,[423][424][425][426]438,[451][452][453][454][455] Moreover, considering CIN as the fuel for genomic diversity, it is important to acknowledge the challenges posed by tumor evolution. This suggests that future research could focus on characterizing the common phenotypes that emerge from various CIN routes.…”
Section: Cin Paradoxmentioning
confidence: 99%